Neuro-Immunity and Gut Dysbiosis Drive Parkinson’s Disease-Induced Pain - Roversi, Katiane; Callai-Silva, Natalia; Roversi, Karine; Griffith, May; Boutopoulos, Christos; Prediger, Rui Daniel; Talbot, Sébastien (Frontiers in Immunology, 2021)
Parkinson's disease (PD) is the second most common neurodegenerative disorder, affecting 1–2% of the population aged 65 and over. Additionally, non-motor symptoms such as pain and gastrointestinal dysregulation are also common in PD. These impairments might stem from a dysregulation within the gut-brain axis that alters immunity and the inflammatory state and subsequently drives neurodegeneration. There is increasing evidence linking gut dysbiosis to the severity of PD’s motor symptoms as well as to somatosensory hypersensitivities. Altogether, these interdependent features highlight the urgency of reviewing the links between the onset of PD’s non-motor symptoms and gut immunity and whether such interplays drive the progression of PD. This review will shed light on maladaptive neuro-immune crosstalk in the context of gut dysbiosis and will posit that such deleterious interplays lead to PD-induced pain hypersensitivity.